Comportamiento del consumidor de los atractivos turísticos de la parroquia Moromoro en la provincia de El Oro - Cabrera Loayza, Kerly María (2015)
Our goal is to evaluate the behavior of the tourism product in the province of El Oro, through a quantitative research of market that will allow the design of strategies and tactics of commercial management in the sector. The methodology that we use is in a way that is consistent with our objective and based on the expressed in the preamble above, the methodology used to carry out our research work is by means of conducting surveys, exploration of media and field work. Conclusions As we have the following:• In conclusion of this development, it is considered to be helping the parish Moromoro to exploit tourism and can therefore be promoting national as well as the outside.• The parish Moromoro has much to offer to the tourists either in the cultural and the natural area between other that will be taken into account as a destination to visit.• Unfortunately, by the ignorance of both the domestic and foreign tourists, of the existence of the tourist attractions such as the Buenaventura Reserve, flora and fauna of the place, the orchids that represent the canton, the gastronomy, among other attractions that would be a place very well exploited if exploited well that is a parish so small and at the same time has much to offer.